Da pedagogia da hospitalidade no turismo ao turismo pedagógico pela hospitalidade - Oliveira, Ana Carolina Rodrigues Melo de (My University, 2014)
This research aims to contribute to touristic enterprises in a sense of having a pedagogical tool to the continuous education for the managers and employees within hospitality relations or even hosting which might transcend the information only and the fortuitous realization of training activities, to be at stake here a relational process to be comprehended and seize. In this sense, we discuss about pedagogy of hospitality , here drawn from the application, in a touristic enterprises, of Operatives Groups (according to Pichon-Rivière, 2005), a theory-methodological based on the constructivist pedagogical paradigm, proposed as a resizing promoter the reconstruction/reframing the hospitality concept and on the relationship establishment of this concept to the professional praxis in tourism and in the touristic praxis. The thoughts presented here are based on the understanding of Hospitality/hosting a established as a phenomenon of the alternation of the poles in interaction (to host and be hosted) and, under this point of view, establishing itself as the foundation axis of the tourism phenomenon. We also present the theoretical assumption that all genuine host loads the pedagogical potential of being an agent of learning, knowledge catalyst, promoter of psychological and cognitive, relational processes transformation. In this universe, this research aims to raise discussion about relations between the hosting phenomenon and the concept of educational tourism. Methodologically, it was developed two Operatives Groups sections, intermediated by performing on the enterprise itself, a specific tourism practice (horse track). The research corpus consists on the subjects verbal manifestations employees and managers of the in loco field enterprise over the operating groups and the guide and tourists responses to the interviews done before and after the track. The discourse analysis was guided by assumptions of the enunciative theory according to Bakhtin (1997), also have appealed to some procedures of the content analysis, according to Bardin (2000). The results link the resizing/reframing, identified/inferred, analysis objects, to the reflexive processes effected on/by the Operative Groups, in which we can find the growing closeness to the concept of hospitality/hosting taken as reference. On the other hand, either directly by the subjects´ responses to interviews or indirectly by the respective operating groups in the manifestations, the tourism, when marked by genuine host relationship, is educational providing boundaries break and thus opening new spaces for transformations and learning.
Esta pesquisa visa contribuir com empreendimentos turísticos no sentido de que disponham de uma ferramenta pedagógica para a formação permanente de gestores e colaboradores no âmbito das relações de hospitalidade ou acolhimento , a qual possa transcender o caráter meramente informativo ou a realização fortuita de atividades de treinamento, por estar aí em jogo processo relacional a ser com preendido e a preendido. Nesse sentido, traz à discussão uma pedagogia da hospitalidade , aqui desenhada a partir da aplicação, num empreendimento turístico, de Grupos Operativos (conforme Pichon-Rivière, 2005), modelo teórico-metodológico com raízes no paradigma pedagógico construtivista, proposto como promotor de redimensionamentos no processo de re construção/ re ssiginificação do conceito de hospitalidade e no estabelecimento de relações deste com a prática profissional em turismo e com a prática turística. As reflexões têm na base o entendimento de hospitalidade/acolhimento como fenômeno instaurado na alternância dos polos em interação (acolhedor e acolhido) e, sob esse prisma, instituindo-se como eixo fundante do fenômeno turístico. Têm também o suposto teórico de que todo acolhimento genuíno carrega o potencial pedagógico de ser agente de aprendizagens, catalizador de saberes, promotor de transformações de processos psicoafetivos, cognitivos, relacionais. Nesse universo, a pesquisa objetiva ainda suscitar discussão sobre relações entre o fenômeno do acolhimento e o conceito de turismo pedagógico. Metodologicamente, desenvolveram-se duas sessões de grupos operativos, intermediadas pela realização, no próprio empreendimento, de uma prática turística específica (trilha a cavalo). O corpus consistiu das manifestações verbais dos sujeitos colaboradores e gestores do empreendimento campo de investigação ao longo dos grupos operativos e de respostas do guia e de turistas a entrevistas realizadas antes e após a trilha. A análise do discurso pautou-se por pressupostos da teoria enunciativa de Bakhtin (1997), tendo recorrido também a alguns procedimentos da Análise de Conteúdo, de acordo com Bardin (2000). Os resultados vinculam os re dimensionamentodos/ re ssignificações identificados/inferidos, objetos de análise, aos processos reflexivos efetivados nos/pelos Grupos Operativos, nos quais se constata crescente aproximação ao conceito de hospitalidade/acolhimento tomado como de referência. Por outro lado, quer diretamente pelas respostas dos sujeitos às entrevistas, quer, indiretamente, pelas respectivas manifestações nos grupos operativos, o turismo, quando marcado por relações genuínas de acolhimento, faz-se ele próprio pedagógico, propiciando ruptura de fronteiras e assim, inaugurando novos espaços de transformações e aprendizagens.
Keywords: TURISMO; Turismo; Hospitalidade/Acolhimento; Empreendimento turístico; Grupos operativos; Turismo pedagógico; Tourism; Hospitality/Hosting; Tourism entreprise; Operative groups; Educational tourism